Monogenic ββ-cell dysfunction in children: clinical phenotypes, genetic etiology and mutational pathways. Issue 4 (August 2008) - Waterfield, Thomas; Gloyn, Anna L
Monogenic diabetes accounts for 1––2% of all cases of diabetes mellitus and presentation is often in childhood. Recognizing the clinical features of monogenic ββ-cell dysfunction prevents misdiagnosis and allows for more effective management and genetic counseling. Monogenic ββ-cell dysfunction is a diverse collection of clinical phenotypes underpinned by common mutational pathways. Mutations affecting the glycolytic glucokinase enzyme, the mitochondria, the KATP channels and transcription factors have been known for some time. Until recently, the role of endoplasmic reticulum stress was underestimated in the pathogenesis of diabetes. It is becoming increasingly clear that endoplasmic reticulum stress is an important etiological factor in the development of monogenic and polygenic diabetes. In this article, we aim to define the etiology of pediatric monogenic ββ-cell dysfunction and provide guidance on the investigation and management of children presenting with monogenic ββ-cell dysfunction.